2004
DOI: 10.1111/j.1551-2916.2004.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low‐Energy Accelerated Ion Bombardment on the Properties of Metal‐Organic Decomposition Derived SrBi2(Ta,Nb)2O9 Thin Films Processed at Low Temperature

Abstract: Ferroelectric SrBi2(Ta,Nb)2O9 (SBTN) thin films were deposited on Pt (200 nm)/TiOx(40 nm)/SiO2 (100 nm)/Si substrates by metal‐organic decomposition. The effects of bombardment from accelerated argon and oxygen ions on the properties of SBTN thin films were investigated. It was found that the argon ion bombardment could decrease the crystallization temperature owing to the increase of internal energy of the films. Also, the oxygen vacancies at the interface between the SBTN film and platinum bottom electrode o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…(c, d) P–E hysteresis loops of SBTN samples treated (c) by Ar + ions, and (d) by the combination of O 2 + /O + and Ar + ions with different annealing times. Reproduced from ref . Copyright 2004 John Wiley and Sons.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…(c, d) P–E hysteresis loops of SBTN samples treated (c) by Ar + ions, and (d) by the combination of O 2 + /O + and Ar + ions with different annealing times. Reproduced from ref . Copyright 2004 John Wiley and Sons.…”
Section: Applicationsmentioning
confidence: 99%
“…It has been demonstrated that the ferroelectric properties can be effectively tuned by the ion irradiation, because the ion irradiation-induced structural distortion/disorder and defects can significantly influence both the polarization and the leakage current. 15,38,39 For instance, Saremi et al 40 grew BiFeO 3 (BFO) thin films on SrRuO 3 /DyScO 3 (110) substrates by PLD. Different concentrations of defects were introduced into the BFO thin films by the helium ion irradiation with an energy of 3 MeV and various ion fluences.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18] In these growth techniques, metal-organic decomposition (MOD), which is categorized in CSD, has the advantages of no requirement for a large facility, low operational cost, and capability of fabricating large-area films. [19][20][21] Due to these reasons, up to date, we have fabricated high sensitive VO 2 microbolometers by MOD. 22,23) However, a VO 2 thin film indicates an abrupt resistance change of several orders of magnitude and thermal hysteresis in the vicinity of 60 °C although it has a high TCR.…”
Section: Introductionmentioning
confidence: 99%